An ethnographic exploration of adolescent homophobic language in a rural religiously-conservative high school. Issue 2 (3rd April 2022) - Bailey, Benjamin M.; Heath, Melissa Allen; Jackson, Aaron P.; Ward, Carol; Black, Amelia; Cooper, Emily; Griner, Derek; Shafer, Kevin
Abstract: Multiple qualitative and quantitative studies have investigated homophobic language and its associated correlates. However, very few studies have approached this phenomenon from an ethnographic methodology. Furthermore, no studies to date have used an ethnography to study this language in a conservative religious community. In this study, the primary researcher conducted semi-structured interviews with 20 randomly selected males, all 12th-grade students attending a rural high school and conducted 102 hours of observations in the high school they attended. Utilizing a phenomenological hermeneutic method, a group of researchers analyzed the interviews and observations. Based on interpretations from this analysis, findings indicated that students used HL to marginalize other students; to both challenge adult authority and emulate admired adults; to get attention and assert authority by using rebellious and taboo language; to explore their sexuality and masculinity; to police sexuality and masculinity within the parameters of religious beliefs and expected roles; and to increase group cohesion. The researchers explored each of these themes and considered how adolescents both shape and are shaped by their within-group culture, their school culture, and their personal beliefs. To conclude, the researchers suggest group-based strategies for a more accepting school culture that decreases adolescents' use of HL.